Aiming for the elimination of viral hepatitis in Australia, New Zealand, and the Pacific Islands and Territories: Where are we now and barriers to meeting World Health Organization targets by 2030. Issue 1 (27th September 2018) - Howell, Jess; Pedrana, Alisa; Cowie, Benjamin C; Doyle, Joseph; Getahun, Aneley; Ward, James; Gane, Ed; Cunningham, Chris; Wallace, Jack; Lee, Alice; Malani, Jioji; Thompson, Alex; et al.
Abstract: Viral hepatitis affects more than 320 million people globally, leading to significant morbidity and mortality due to liver failure and hepatocellular carcinoma (HCC). More than 248 million people (3.2% globally) are chronically infected with hepatitis B virus (HBV), and an estimated 80 million people (1.1% globally) are chronically infected with hepatitis C virus (HCV). In 2015, more than 700 000 deaths were directly attributable to HBV, and nearly 500 000 deaths were attributable to HCV infection; 2–5% of HBV‐infected people develop HCC per annum irrespective of the presence of cirrhosis, whereas 1–5% HCV‐infected people with advanced fibrosis develop HCC per annum. The rapidly escalating global mortality related to HBV and HCV related viral hepatitis to be the 7th leading cause of death worldwide in 2013, from 10th leading cause in 1990. Australia, New Zealand, and Pacific Island Countries and Territories fall within the World Health Organization Western Pacific Region, which has a high prevalence of viral hepatitis and related morbidity, particularly HBV. Remarkably, in this region, HBV‐related mortality is greater than for tuberculosis, HIV infection, and malaria combined. The region provides a unique contrast in viral hepatitis prevalence, health system resources, and approaches taken to achieve World Health Organization global elimination targets for HBV and HCV infection. This review highlights the latest evidence in viral hepatitis epidemiology and explores the health resources available to combat viral hepatitis, focusing on the major challenges and critical needs to achieve elimination in Australia, New Zealand, and Pacific Island Countries and Territories.